How Does Compost Amendment Affect Stevia Yield and Soil Fertility? - El Hocine Hirich; Brahim Bouizgarne; Abdelmjid Zouahri; Oumaima Ibn Halima; Khalid Azim (Environmental Sciences Proceedings, 2022)
Stevia (Stevia rebaudiana) is a plant species belonging to the family Asteraceae. It contains natural intense sweeteners while presenting low carbohydrate content. Its insignificant effect on blood glucose makes its consumption possible for diabetic and hypoglycemic diets. Chemical fertilizers have a negative impact on the stevia leaves quality. Organic farming has become essential in producing medicinal plants such as Stevia to boost stevia growth with stevioside and rebaudioside-A content. The purpose of this study was to evaluate the effect of four compost doses, i.e., 0, 10, 20, and 30 t/ha on Stevia yield and soil fertility. This experiment was conducted in the Melk Zhar experimental domain, Belfaa of the National Institute of Agronomic Research (INRA), Agadir, Morocco during the period of February-June 2020. The obtained results revealed that increased compost doses significantly increased yield and soil fertility i.e., phosphorus; P, potassium; K and organic matter; OM contents. The highest yield (2.19 t/ha) was observed under treatment using 30 t/ha of compost followed by 20 t/ha (1.67 t/ha), and the lowest (1.50 t/ha) under control conditions. The highest OM content (1.02%) was found under treatment with 30 t/ha of compost while the lowest (0.85%) was under the control. The soil analysis also showed that the application of compost at 20 t/ha resulted in the highest P (28.68 ppm) and K (125.5 ppm). In the light of finding, it is concluded that the application of compost at 30 t/ha is the most effective recommended rate for improving Stevia yield and soil fertility.